Augmented reality with a path to the metaverse - Ipince, Pablo (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This paper presents the implementation of an innovative augmented reality (AR) application in logistics education, with the aim of evaluating its impact on teaching methods and the student learning experience. The project was developed at INACAP, Maipú campus, through an immersive simulation of a Distribution Center (DC) using Oculus devices, aligning withpedagogies focused on active learning. The research adopted a mixed-methods approach with a multi-sequential design, employing interviews, post-workshop questionnaires, and analysis of academic documents. Students participated in interactive simulations that facilitated the application of theoretical concepts and the development of skills such as leadership, teamwork, and decision-making. The results showed a significant increase in motivation, participation, and understanding of logistics content, reflected in improved grades and high reported satisfaction. It is concluded that this initiative not only enhances the teaching of logistics but also proposes a didactic model that can be replicated in other disciplines. Furthermore, it envisions the integration of the metaverse as an educational platform, expanding the possibilities for interaction and collaborative learning in multidimensional virtual environments.